2021
DOI: 10.1111/jen.12962
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate chemosensory genes by antennal transcriptome analysis in an ectoparasitoid wasp

Abstract: Iseropus (Gregopimpla) kuwanae Vlereck (Hymenoptera: Ichneumonidae) is an ectoparasitoid wasp that attacks the larvae of Rondotia menciana Moore (Lepidoptera: Bombycidae), which is a major pest harming mulberry trees in China. In this study, we obtained the antennal transcriptome dataset of I. kuwanae using RNA‐Seq technology. A total of 22,090,144 clean reads were generated, and 21,802 unigenes were assembled. Among them, 11,546 (52.96%) unigenes were matched in the NCBI non‐redundant protein database (E‐valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The number of SNMPs in various species ranges from two (Drosophila melanogaster) [78] to sixteen (Onthophagus taurus) [79]. A total of eight SNMPs were identified in B. dioryctriae, which is much more than the number of SNMPs found in Iseropus kuwanae (2) [16] and M. mediator (2) [80], suggesting that BdioSNMPs have large species expansions among Hymenoptera [81]. In general, numerous studies have found that most insects have two types of SNMPs, namely SNMP1 and SNMP2 [50], and all identified BdioSNMPs belong to the SNMP1 subfamily (Figures 7 and S9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of SNMPs in various species ranges from two (Drosophila melanogaster) [78] to sixteen (Onthophagus taurus) [79]. A total of eight SNMPs were identified in B. dioryctriae, which is much more than the number of SNMPs found in Iseropus kuwanae (2) [16] and M. mediator (2) [80], suggesting that BdioSNMPs have large species expansions among Hymenoptera [81]. In general, numerous studies have found that most insects have two types of SNMPs, namely SNMP1 and SNMP2 [50], and all identified BdioSNMPs belong to the SNMP1 subfamily (Figures 7 and S9).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing technologies have developed rapidly over the past decade [16], and have been widely used to identify chemosensory genes in many insects [17]. In Hymenoptera, an enormous number of chemosensory genes from various species have been reported, and most of them have been identified through antennal transcriptomes.…”
Section: Introductionmentioning
confidence: 99%
“…pulchricornis adults and collected with three replicates. Total RNA was isolated using the RNAiso Plus reagent (Takara, Dalian, China), and the reverse transcription was performed using the HiScript III 1st Strand cDNA Synthesis Kit (+gDNA wiper) (Vazyme Biotech Co., Ltd.) on the thermal cycler . The sequence analysis was performed using SignalP-6.0 server (), WebLogo online program (), and MEGA-X software .…”
Section: Methodsmentioning
confidence: 99%